ANALISIS KESALAHAN BERBAHASA MAHASISWA IKIP SILIWANGI DALAM LITERASI MEDIA - Ainun Rismawati Dewi Rais (IKIP Siliwangi, 2020)
This study describes the types of errors in language towards students, errors and absorptive language in IKIP Siliwangi Bandung students. In writing status on social media networks (WhatsApp and Instagram). The object of research is IKIP Siliwangi Bandung students. The subjects in this study were 10 students. This study intends to find out the knowledge of students in using Indonesian language that is good and right, the second aims to explain the forms of language errors. The data source in this study uses Indonesian status recording (screenshoot) and observation. The data in this study are words or sentences in whatsapp and instagram status. The method of listening or using the record technique and note technique is a suitable method in collecting data in this study and the research method used in this research is descriptive qualitative research method, the research method is carried out in natural conditions and is analytical. Data analysis was carried out by the researcher with the first collecting data with (screenshoot), the second step the researchers conducted data reduction, and concluded the results of the data. The results of this study concluded that the errors in language that are often done by students who use many of the words abbreviations, relaxed, alay included in the area and the nature of language errors, namely phonological errors, fossil errors and syntax errors. Furthermore, there have been 23 data collected. Student data in social media networks, it was found that student writing in social media status there were errors in language. Mistakes that are often written by students in writing on social media networks are fossil errors. Language mistakes are mistakes that are not realized and are considered not wrong by students.